Empirical test of the trust – performance link in international alliances context - Silva, Susana Costa e (2011)
This paper focuses on the influence of trust on international alliances performance. Trust has been theoretically recognised to produce positive effects on alliances success. However, the link has rarely been empirically proven. We elaborate on the major difficulties that may explain this and propose a model for the understanding of that influence, where trust antecedents are also considered. The link is validated through primary data collected from 232 international alliances of Portuguese firms and analysed through structural equation modelling.